Clinical Significance of Electroencephalography in Children with Specific Learning Disorders - Aksoy, Erhan; Öztoprak, Ülkühan; Sabancı, Murat; Çetinkaya, Miray; Genç-Sel, Çiğdem; Kayılıoğlu, Hülya; Aksoy, Ayşe; Yüksel, Deniz (Journal of Pediatric Epilepsy, 2019)
A specific learning disorder (SLD) is a neurodevelopmental disorder in which academic skills, such as reading, writing, and mathematics ability, are below the expected range. This study was conducted to determine the relationship between spike-wave index and SLD in children. We recruited 110 child psychiatry outpatients (38 girls, 72 boys) with SLDs for this study between January 2015 and March 2018. The mean ± standard deviation patient age was 9.17 ± 1.87 years. Electroencephalography (EEG) findings were abnormal in 20.9% of children. We found that children with expressive language delay and who were born prematurely had a significantly higher risk of spike-wave index. Attention deficit/hyperactivity disorder was present in 55.5% of children with SLD. This comorbidity was significantly higher in children with a history of prenatal smoking exposure or premature birth. The EEG findings were particularly important in cases of SLD in children who were born prematurely and had expressive language delay. The spike-wave index is a potential marker of SLD and can be easily and noninvasively detected by EEG.
Keywords: specific learning disorder; children; electroencephalography